Exploring tripartite praxis for the REDD + forest climate change initiative through community based ecotourism. Issue 3 (3rd March 2020) - Wearing, Stephen; McDonald, Matthew; Schweinsberg, Stephen; Chatterton, Paul; Bainbridge, Tahnee
Abstract: Reducing Emissions from Deforestation and Degradation (REDD+) is a United Nations programme initiated in 2008 with the aim of mitigating climate change through the preservation of the world's existing forest stocks. One of the challenges in its successful implementation has been community involvement in its design, implementation, monitoring and evaluation. The purpose of this study is to assess what REDD + can learn from the experience of Community-Based Ecotourism (CBET), which operates under many of the same conditions. A critical review of the related literature using the Scopus database was undertaken using three search strings including "REDD+" (2, 913 listings), "community-based ecotourism" (113 listings) and "REDD + and tourism" (6 listings) to identify the variables and themes related to each. Despite the significant increase in the number of publications on REDD + since 2008, only one was specifically related to ecotourism. We argue that CBET understood as a form of social capital can function as an enabling platform for REDD+, in particular its implementation of international conservation policy by working with local communities/indigenous peoples and business stakeholders, referred to here as the "tripartite praxis". We demonstrate how CBET can act as a basis from which to guide internationally driven incentive-based conservation policy and community entrepreneurship within a social capital framework.